Pengaruh Brand image Dan Perilaku Konsumen Terhadap Keputusan Pembelian Mie Ayam Sinar Utama - Hutagalung, Mhd Rezi Ramadhan; Rafiki , Ahmad; Tarigan , Eka Dewi Setia; Tobing, Fitriani (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to determine "The Influence of Brand Image and Consumer Behavior on Purchasing Decisions of Mie Ayam Sinar Utama". This type of research is associative, namely a study that is to find out whether there is a relationship between two variables, where the variables are measured using a Likert scale. The population in this study were consumers at Mie Ayam Sinar Utama Medan with a sample of 96 respondents taken from some consumers from the existing population. And by using the Slovin formula technique. Data processing was carried out using SPSS software, with descriptive analysis and multiple regression analysis hypothesis testing. Based on the results of the t test, it can be seen that the t count on the brand image variable of 3,749 is greater than the t table of 1,984 with a probability of t, namely sig 0.000, smaller than the significance of 0.05..Based on these values, the brand image variable has a positive and significant effect on purchasing decisions. In the t-count variable of 4,788 and t-table of 1984 with a probability of t, namely sig 0.000, which is smaller than the significance limit of 0.05, the Consumer Behavior variable partially has a positive and significant effect on the purchasing decision variable. Based on the results of the F test, the F-count value of 31,247 with sig 0.000 <0.05 indicates that Ho is rejected and Ha is accepted, meaning that brand image and Consumer Behavior simultaneously have a positive and significant effect on purchasing decisions.